Blood and serum activities in commercial broiler chickens fed with partial replacement of soybean and dicalcium phosphate feeds supported with microbial phytase - JADHAV, N V; SURANAGI, M D; ANJANEYA, S N; CHANDRA, PRAKASH; MALLIKARJUNAPPA, S (The Indian Journal of Animal Sciences, 2011)
The study was undertaken to evaluate the efficacy of phytase incorporation in feeds of commercial broilers partially replaced for soybean meal (SBM) and dicalcium phosphate (DCP) with alternative feedstuffs on Hb, serum alkaline phosphatase (ALP) and serum mineral profile in broilers at 3 and 5 weeks of age. The results revealed similar positive trend of effects at both the ages for all the 3 replacements of SBM with sunflower meal (SFM), safflower meal (SAFFM) and sesame cake accompanied by DCP substitution with limestone. There was highly significant increase in blood haemoglobin (Hb) level of phytase supplemented broilers when compared with non-supplemented birds. The serum ALP levels were highly significantly enhanced in all the phytase added groups in comparison with broilers without phytase. Further, phytase feeding had significant positive effect on serum mineral (Ca, P, Cu, Zn, Fe and Mg) levels in broiler chickens as compared to birds without phytase feeding. All the improved values of aforesaid parameters studied were at par with figures from control group. Â